Implementation Strategies of Gamification in Elementary School Learning: A Systematic Literature Review - Yunita, Septi; Munir; Syawalahayati, Sekar; Aryanti, N. Sinta Mustika (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2026)
Elementary school learning often faces problems related to low attention, weak learning motivation, and limited active participation during classroom activities. These issues commonly arise from teacher-centered instruction and a lack of varied learning experiences. One approach considered to address these problems is gamification, which integrates game elements into learning activities to increase student engagement. This study aims to identify the forms of gamification used in elementary school learning and analyze implementation strategies based on previous empirical studies. The research employed a Systematic Literature Review method by reviewing eleven selected articles from the Scopus and Taylor & Francis Online databases, published between 2020 and 2025, written in English, and available in full-text format. Data analysis was conducted through narrative synthesis. The findings show that gamification is implemented through digital learning platforms, interactive physical tools, and narrative-based classroom activities. Common implementation strategies include designing learning tasks in progressive levels, providing rewards, giving instant feedback, and using stories or characters to contextualize learning materials. The study concludes that gamification has the potential to improve student motivation and participation when game elements are planned systematically and aligned with learning objectives